THE EFFECT OF ENGLISH GAMES TO IMPROVE SPEAKING SKILL AND MOTIVATION OF CLASS X SENIOR HIGH SCHOOL STUDENTS - LIDIA APRILIANA NAINGGOLAN; JELITA ELPINA SIALLAGAN; RENATA RK SITUMORANG (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2022)
Teaching speaking is very important for foreign learners. Through speaking skills, many things can be achieved. But in fact, there are still many students at the high school level who have difficulty speaking English. This makes them passive in the classroom and subsequently do not get a career advancement in the world of work. The purpose of this study was to test whether English games could improve speaking skills and student motivation in first grade at SMA N 1 Dolok Batu Nanggar and to determine the factors that influence the improvement of speaking skills and learning motivation. This research is included in classroom action research. Data was collected through assessment, observation, and interviews. Assessment is used to assess speaking; Observation sheets were used to assess students' learning motivation, then interviews and field notes were used to obtain further information. The findings of this study have answered the research question, that the use of English games can improve students' speaking skills and learning motivation at SMA N 1 Dolok Batu Nanggar. This technique is very useful for improving students' speaking skills and learning motivation. This technique should be applied in SMA N 1 Dolok Batu Nanggar, and it is suggested to schools with poor speaking skills and low learning motivation to apply and develop this method to overcome these students' English learning problems.